The Archetype of the Leader-Hero in the Novels "Genghis Khan" and "Bilge Khagan": A Comparative Analysis. - Djuraeva Farahbonu Ismatillo-kizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2026)
Literary conceptualization of absolute power and historical agency necessitates a rigid archetypal framework. This study deconstructs the specific structural and semantic paradigms defining the "leader-hero" archetype within the historical narratives centered on Genghis Khan and Bilge Khagan. Utilizing a continuous sampling method on a textual corpus of 1,250 discrete micro-contexts, the research operationalizes Jungian psychoanalytic literary theory alongside quantitative semantic parsing. The primary objective is to map the divergent cognitive trajectories employed by authors to legitimize and humanize nomadic sovereign figures. Extraction and categorization of behavioral markers yielded statistically significant variations in archetypal dominance. The representation of Genghis Khan is heavily localized within the "Destroyer-Conqueror" and "Shadow" matrix, prioritizing lexemes of subjection and elemental force. Conversely, the literary architecture surrounding Bilge Khagan prioritizes the "Sage-Lawgiver" and "Patriarch" configurations, anchoring his authority in cultural preservation and monumental memory. Analyzing these quantitative disparities elucidates how distinct historical memory regimes dictate the literary reconstruction of leadership. The findings establish a robust comparative methodology for evaluating Eurasian historical prose, shifting the critical paradigm from historiographic verification to structural-mythological analysis. Implementing these structural dichotomies into university literature curricula will substantially elevate the analytical competencies of philology students.